MEMAHAMI AL-QUR'AN SEBAGAI AYAT ATAU SURAT MAKKIYYAH DAN MADANIYYAH - Fatihah Izzatul Yusrany (Majalah Ilmu Pengetahuan dan Pemikiran Keagamaan Tajdid, 2020)
This article explains of a verse or letter which is included in the category of makkiyah and madaniyah. Where are the various commands or prohibitions in sharia bases on makkiyah and madaniyyah arguments. Al-Qur'an is word of Allah SWT that was sent down to Rasulullaah SAW througt of angel Jibril. The period of descent is divided into two periods, namely before and after hijrah Rasulullaah SAW. In general, the verses that were revealed and Mecca and its surrounding before the hijrah and called Makkiyah, and the verses that were revealed in Median and its surrounding after the hijrah and called Madaniyah. This paper focuses on the meaning, kategories Makkiyah and Madaniyah, the basis for determinatio, characteristics, uses, and benefit, of studying them. This clarifications of the koran was not carried out by Rasulullaah SAW, but rather ojtihad from the scholars'. This clarifications is very important to understand the surah and verses of the Al-Qur'an in what context and how they were revealed. The research method used is literature review, with qualitative data and analysis also with a critical study approach to makki and madani research. By conducting a careful study of books or literature related to the topics discussed. Reading sources are an essential part of research support.